2017
DOI: 10.7716/aem.v6i2.472
|View full text |Cite
|
Sign up to set email alerts
|

HYDROFLASH: A 2-D Nuclear EMP Code Founded on Finite Volume Techniques

Abstract: The basic mechanisms that govern the generation of an electromagnetic pulse (EMP) following a nuclear detonation in the atmosphere, including heights of burst (HOB) relevant to surface bursts (0 km), near surface bursts (0-2 km), air bursts (2-20 km) and high-altitude bursts (> 20 km), are reviewed. Previous computational codes developed to treat the source region and predict the EMP are discussed. A new 2-D hydrodynamic code (HYDROFLASH) that solves the fluid equations for electron and ion transport in the at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Since the 1960s, scientists have found that the nuclear explosion was a strong source of the electromagnetic pulse (e.g., Berthold et al., 1960; Bomke et al., 1960, 1964; Casaverde et al., 1963; Cotterman, 1965; Crook et al., 1963; Dinger & Garner, 1963; Field & Greifinger, 1967; Latter & LeLevier, 1963; Wittwer et al., 1974). The majority of previous studies on HEMP have used γ‐rays rather than X‐rays as the energy source (e.g., Leuthiiuser, 1992; Li et al., 2020; Longmire, 1978; Meng, 2013; Roussel‐Dupré, 2017; Zhang & Zhang, 2018). This is appropriate for observers situated below 40 km in altitude (Higgins et al., 1973; Karzas & Latter, 1965; Price, 1974), because X‐rays have been absorbed within several tens of meters from the burst, thus only energetic γ‐rays with several kilometers free path can proceed at low altitudes.…”
Section: Introductionmentioning
confidence: 99%
“…Since the 1960s, scientists have found that the nuclear explosion was a strong source of the electromagnetic pulse (e.g., Berthold et al., 1960; Bomke et al., 1960, 1964; Casaverde et al., 1963; Cotterman, 1965; Crook et al., 1963; Dinger & Garner, 1963; Field & Greifinger, 1967; Latter & LeLevier, 1963; Wittwer et al., 1974). The majority of previous studies on HEMP have used γ‐rays rather than X‐rays as the energy source (e.g., Leuthiiuser, 1992; Li et al., 2020; Longmire, 1978; Meng, 2013; Roussel‐Dupré, 2017; Zhang & Zhang, 2018). This is appropriate for observers situated below 40 km in altitude (Higgins et al., 1973; Karzas & Latter, 1965; Price, 1974), because X‐rays have been absorbed within several tens of meters from the burst, thus only energetic γ‐rays with several kilometers free path can proceed at low altitudes.…”
Section: Introductionmentioning
confidence: 99%
“…Several 1‐D simulations (Meng, 2013; Wei & Kiang, 2016) and 3‐D simulations (Friedman et al, 2015, 2016; Kruger, 2012, 2016) were introduced. Investigations of conductivity models were carried out (Pusateri et al, 2016; R. Roussel‐Dupré, 2017).…”
Section: Introductionmentioning
confidence: 99%